PENGARUH LATIHAN LIFE KINETIK TERHADAP HASIL KETERAMPILAN NOMOR SLALOM CABANG OLAHRAGA ARUNG JERAM ATLET PUTRI - Sandi Fajri Ramdani, - (2023)
This research departs from the problem of the decline in achievement in the slalom number of rafting sports.. This study is conduted to determine "the effect of life kinetic training on the results of slalom number skills in women's rafting sports". The research method used is an experimental research method using the Pre-test Post-test control group Design. The data collection technique is carried out by giving an initial test/pre-test. Then treatment with the Life Kinetic training model is given. The data processing technique used is the Non-parametric Test. The population used in this study were women athletes of slalom rafting category in Bandung City. The sample that the writer uses is total sampling. The sample in this study are 16 athletes, which divided into 4 teams. The research is conducted for 4 weeks in 12 meetings. The results of this study indicate that there is a significant effect of life kinetic training on the results of slalom category skills to the women athletes in the rafting sport.